Penggunaan Media Pembelajaran Bunga Pengurangan terhadap Hasil Belajar Matematika di SDN Gayamsari 02 - Dika Rakhmah Andirawati; Ferina Agustini; Espiyati Espiyati (Departement of Mathematics Education, 2024)
This study aims to determine the effect of using flower subtraction learning media on the mathematics learning outcomes of first grade students at SDN Gayamsari 02. This study uses a qualitative approach with a case study research design. The subjects of the study were first grade students of SDN Gayamsari 02. Data were collected through observation, tests, and interviews. The results of the study showed that the flower subtraction learning media had a positive impact on the learning outcomes of first grade students at SDN Gayamsari 02. This is indicated by the good learning outcomes of students on the final test after using the flower subtraction learning media. In addition, the results of observation and interviews showed that students were more enthusiastic and active in participating in mathematics learning when using the flower subtraction learning media.